Evaluation of the foot health with baropodometric analysis of acromegaly patients followed after pituitary surgery (Bangladesh Journal of Medical Science, 2024)
Background: The exposure to growth hormone (GH) and increase in insulin-like growth factor 1 (IGF-1) in acromegaly can cause various clinical findings related to the cardiovascular, respiratory, and musculoskeletal systems. GH exerts its anabolic effects directly or indirectly through IGF-1, by increasing cell proliferation and maturation in various tissues, including bone, cartilage, skeletal muscle, and tendons. The aim of this study is to analyze these changes using baropodometric gait analysis.Methods: Our study was conducted with a sample of 41 acromegaly patients and 42 control group individuals. Static, dynamic, and stabilometric baropodometric analyses were performed, as well as podoscanner analysis.Results: According to the dynamic and static baropodometric analyses of both groups, the standing load distribution and stabilometric Romberg index findings were similar. However, the acromegaly group showed a higher prevalence of pes planus findings compared to the control group (p